Dynamic System of Flood Disaster Management in Makassar City Using the Analysis AHP Method - Syawal, Wahyu Dzunaid; Sideng, Uca; Arfan, Amal (JPG (Jurnal Pendidikan Geografi), 2025)
Flooding is one of the problems frequently faced by the people of Makassar City. This natural disaster is highly destructive and detrimental, affecting infrastructure, livelihoods, and the social conditions of the community. This study employs the Analytic Hierarchy Process (AHP) method to evaluate the criteria influencing flood management, focusing on population size and the role of stakeholders. Data were collected through questionnaires distributed to experts from various agencies, including the Meteorology, Climatology, and Geophysics Agency (BMKG) Region 4 Makassar, the Environmental Agency of Makassar City, the Public Works Agency of Makassar City, the Jeneberang River Basin Office, and the Regional Disaster Management Agency (BPBD) of Makassar City.The results of the study indicate that AHP data processing yields a comparison matrix value for flood disaster risk management and mitigation. The most dominant influencing criterion is the role of stakeholders, accounting for 54%, followed by population size at 27%, land development rate at 13%, and environmental quality at 6%. The analysis of the management dynamics model shows that the risk and impact of flooding have an interrelated relationship among the four categories. The role of stakeholders has the greatest contribution in influencing the categories of population size, land development rate, and environmental quality.